Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.112.144.1990
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis and Interstitial-Water Chemistry at the Peruvian Continental Margin—Major Constituents and Strontium Isotopes

Abstract: Two distinct hydrogeochemical regimes currently dominate the Peruvian continental margin. One, in shallower water (150-450 m) shelf to upper-slope regions, is characterized by interstitial waters with strong positive chloride gradients with depth. The maximum measured value of 1043 mM chloride at Site 680 at ITS corresponds to a degree of seawater evaporation of ~2 times. Major ion chemistry and strontioum isotopic composition of the interstitial waters suggest that a subsurface brine that has a marine origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 42 publications
7
82
0
3
Order By: Relevance
“…These include clay mineral dehydration reactions, particularly the smectite-to-illite transition that occurs at approximately 1.5 km depth [24], differential-stress-induced smectite dehydration [25], and the opal-A to opal-CT transformation [26]. Evidence for migration of low salinity water is found along the Peruvian margin [27], along the décollement at the Costa Rica margin [28,29], and the Barbados margin [30].…”
Section: Resultsmentioning
confidence: 99%
“…These include clay mineral dehydration reactions, particularly the smectite-to-illite transition that occurs at approximately 1.5 km depth [24], differential-stress-induced smectite dehydration [25], and the opal-A to opal-CT transformation [26]. Evidence for migration of low salinity water is found along the Peruvian margin [27], along the décollement at the Costa Rica margin [28,29], and the Barbados margin [30].…”
Section: Resultsmentioning
confidence: 99%
“…45). Such high concentrations of chloride (630 mM) are unusual; in other forearcs chloride concentrations decrease below seawater values (Gieskes et al, 1990a;Kastner et al, 1990). In addition, sodium and potassium concentrations decrease rapidly below depths of 75 and 125 mbsf, suggesting that igneous rocks at the base of the site are a sink for these elements.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum chloride concentration is -14% greater than seawater at only -175 mbsf. The cause of this high chloride concentration is unknown; other convergent margin pore fluids are usually characterized by chloride concentrations less than seawater values (Gieskes et al, 1990a;Kastner et al, 1990;Mottl et al, in press). At least two processes may increase chloride concentrations: (1) hydration of basement rocks and sedimentary minerals, particularly volcanic ash, and (2) ion exclusion as water flows through semipermeable clay 400 0.0 0.5 1.0 Total organic carbon (%) Figure 14.…”
Section: Chlorinity and Salinitymentioning
confidence: 99%
“…However, this limits the end-member 87 Sr/ 86 Sr ratio only to -0.70875 . Work during ODP Leg 112 (Peru margin), where high chlorinities at depth were also observed (Kastner et al, 1990;Elderfield et al, 1991), showed that profiles were consistent with the mixing of an evolved brine associated with evaporite formation with the seawater as it was transported at depth within the marginal sediments. Thus, the high-chloride end-member at a particular site may be itself a mixture of brine and seawater that is in diffusive communication with the overlying pore-water system.…”
Section: The Influence Of Evaporitesmentioning
confidence: 97%
“…However, evidence for large-scale fluid flow was not found at previous ODP sites adjacent to carbonate platforms, such as in the Bahamas (Swart and Guzikowski, 1988) and the Maldives (Swart and Burns, 1990). Another topic of interest was that previous work on hemipelagic sediments drilled by ODP has shown evidence for the presence of evaporites at depth Kastner et al, 1990) that can influence diagenetic processes.…”
Section: Introductionmentioning
confidence: 93%